ENHANCEMENT OF SOLUBILITY AND DISSOLUTION CHARACTERISTICS OF ETORICOXIB BY SOLID DISPERSION TECHNIQUE USING DIFFERENT GRADE OF PEG CARRIER USING (Journal of Pharmaceutical Negative Results, 2023)
In this research work based on solubility enhancement method useful of use less water soluble drug of etoricoxib pure drug and use with water soluble carrier different PEG3350,PEG4000,PEG6000,PEG8000,PEG 20000 grade and drug and water soluble carrier ratio 1:1,1:2,1:4 and 1:6 and urea in different ratio1:1,1:2,1:4 and 1:6 and use physical fusion method and evolution of solid dispersion and I was observed drug solubility increases it useful in development of novel formulation use though solid dispersion method drugs that are poorly water soluble, which accelerates dissolving and can significantly improve bioavailability. Amorphous drug forms typically have substantially higher enthalpy than their crystalline counterparts. By transforming the medicine into an amorphous molecular dispersion using a hydrophilic carrier matrix, crystallization can be prevented. During the formulation development process, one of the most difficult aspects of drug delivery is enhancing the bioavailability of the weak aqueous drug. The pace and quantity of the drugs that leaves the dose form and enters the systemic circulation before it reaches the site of action to have the desired effect is known as bioavailability.